An Automatic Sorting Control System Applied to Logistics Industry - YANG Yu; YANG Lei; ZHANG Xiao-nan (Journal of Harbin University of Science and Technology)
Aiming at the problems of high sorting error rate and low sorting efficiency in manual logistics transshipment mode, it is difficult to meet the increasing logistics demand of Chinese society. Therefore, this paper proposes an automatic cargo sorting system, which can be applied to the automatic sorting and sorting of goods in the logistics industry. Compared with the traditional manual sorting and sorting methods, the system can not only significantly improve the sorting efficiency and classification of goods. The accuracy rate and the saving of a large amount of labor costs have important application value for promoting the development of automation and intelligence in the logistics industry.